Complete LCA of battery electric and conventional fuel vehicles for freight trips. (September 2022) - Middela, Mounisai Siddartha; Mahesh, Srinath; Kancharla, Surendra Reddy; Ramadurai, Gitakrishnan; Perme, Rokom; Sripada, Subrahmanya Kiran; Devi, Gayathri
Abstract: Estimating emissions savings from alternative vehicular technologies is essential to streamline urban freight transport policy. We estimate freight emissions in the city of Chennai, India using real-world emission factors obtained from on-board emission measurement systems and trip characteristics collected through an establishment survey. India recently enforced Bharat Stage VI (BS-VI) emission standards and both the central and multiple state governments have introduced battery electric vehicle (BEV) policies. To understand potential benefits, we estimate the emission savings with BS-VI vehicles and BEVs for freight delivery. The BS-VI vehicles reduce tailpipe CO emissions by 20.3%, and HC+NO x emissions by 74.5%. The GHG emission saving in CO2 equivalents with BEVs is 50.3%, which increase with a greener energy mix, improved transmission and distribution efficiency, cleaner battery production, and more lifetime vehicle kilometres. BS-VI adoption can deliver significant emission reduction until BEVs and charging infrastructure scale up. Graphical abstract: Highlights: Emission estimation is based on freight data from establishment surveys. Real-world emission factors of two-wheelers, three-wheelers, and trucks are considered. Latest emission standard vehicles reduce CO and HC + NO x emissions by 20.3% and 74.5%. 50.3% of the complete life cycle GHG emissions can be reduced with battery electric vehicles. Sensitivity analysis identifies opportunities to reduce emissions from battery electric vehicles further.